Cluster–Head Switching Algorithm Based on Node Temperature in Wireless Body Sensors Networks - Ferreira, Creyton B. de M.; Guedes, Raphael M.; Henriques, Felipe da R. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
In this work, we propose a cluster-head switching scheme based on the temperature of the node, applied to a Wireless Body Sensor Network with clusters topology. Periodically, each node verifies its temperature, and when it reaches an upper bound, its transmission is stopped and other route is used for packets forwarding until the sink. Unlike some methods found in literature, the temperature control is realized at the application layer. Thus, there is a freedom of choice in the routing protocols to be used. Simulations were performed by using the Castalia/Omnet++ simulator, and metrics such as the energy consumption during the cluster-head change, besides the packets loss rate based on the movement of the sink node. In the simulations, we consider the LEACH routing protocol over the IEEE 802.15.4 and IEEE 802.15.6 networks, and we observed that the IEEE 802.15.6 standard presents a lower energy consumption, and a smaller packets loss rate considering a mobile sink.